PEMBERDAYAAN PENYANDANG DISABILITAS DI PROVINSI KALIMANTAN TIMUR - Sy Nurul Syobah (NUANSA: Jurnal Penelitian Ilmu Sosial dan Keagamaan Islam, 2018)
Dissability issue has become a trending topic which is always interesting to be discussed. Not only in the developing country but also in the developed countries as well. It is so because people with dissability belong to a minority group whose right have not been noticed greatly by the government. Dissability is a concept which has not been realized to be exist in the society although it can be seen clearly in someone’s life. One way to fullfill the people with dissability’s welfare is through a holistic empowerment  where they are involved as the main part but not the object. Therefore, this research are aimed at examining (1) how far is the people with dissability’s involvement in planning and implementing the empowerment programs, and (2) how are the effect of empowerment programs on the welfare of people with dissability sosial group in East Kalimantan. The research result shows that the people with dissability in Kalimantan have not been involved yet in the issue of their welfare. Besides, the empowerment programs created by the government of East Kalimantan have not guarateed the people with dissability’s welfare.